A novel fluorescein sodium-based screening platform for the identification of sphingoid base-producing Wickerhamomyces ciferrii mutants - Kang, Jun Su; Lee, Seong-Rae; Lee, Minju; Kim, Eunha; Lee, Pyung Cheon (Frontiers in Bioengineering and Biotechnology, 2025)
The efficient identification of microbial strains capable of producing rare sphingoid bases, such as sphingosine and sphinganine, is critical for advancing microbial fermentation processes and addressing increasing industrial demands. Wickerhamomyces ciferrii, a non-conventional yeast, naturally overproduces tetraacetyl phytosphingosine (TAPS); however, the production of other valuable sphingoid bases, including sphingosine, sphinganine, and triacetyl sphingosine, remains a key target. In this study, we developed a novel screening method utilizing fluorescein sodium, a selective fluorescent dye that specifically reacts with non-acetylated sphingoid bases—sphinganine, sphingosine, and phytosphingosine—while exhibiting no reactivity with TAPS. A mutant library of W. ciferrii was generated via gamma-ray mutagenesis and screened using fluorescence-activated cell sorting (FACS). Mutants exhibiting high fluorescence intensity, indicative of non-acetylated or partially acetylated sphingoid base production, were isolated through three rounds of sorting and further validated via HPLC analysis. This approach successfully identified three mutant strains: P41C3 (sphingosine-producing), M01_5 (sphinganine-producing), and P41E7 (triacetyl sphingosine-producing). Among them, the P41C3 mutant achieved a sphingosine titer of 36.7 mg/L during shake-flask cultivation, accompanied by a significant reduction in TAPS production, indicating a redirection of metabolic flux. This study demonstrates the utility of fluorescein sodium as a selective screening dye for sphingoid base-producing strains and establishes an effective platform for the metabolic engineering of W. ciferrii to enhance the production of industrially significant sphingolipids.